Knowledge score regarding contraceptive methods among married women in urban areas of Belagavi - K., Kruthika; Metgud, Chandra S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Increase in population growth is one of the biggest problems faced from many developing countries including India. Contraception plays an important role to halt population growth but is one of the most deserted part of maternal and child health care. Even after India being the first country to launch the family planning programme still the prevalence of contraceptive use is low which in turn increases the maternal and infant mortality rate. Objectives: 1.To assesses the knowledge score regarding contraceptive methods. 2. To study the association between knowledge and practice of contraception Methods: A community based cross sectional study was conducted among 600 married women aged 15 to 44 years residing in three urban field practice area of Department of Community Medicine, J.N. Medical College, Belagavi. Information was collected using pretested, predesigned questionnaire and knowledge scoring was done. Results: In the present study, the prevalence of contraceptive use was 58.8%, among these 16.0% were condom user,18.9% were using IUCD, 4.3% using rhythm method, 3.3% using OCPs and 16.3% were practicing sterilization method. According to knowledge score, sterilization and Condom methods had the highest scores and injectables least. In general as the knowledge score increased, the practice of contraception also increased. Conclusions: By the results we can conclude that increase in knowledge regarding contraceptives will increase the usage. This can be done by proper counselling for both husband and wife and providing proper information regarding contraceptive by removing their blind beliefs.